USING ACTION SONG TO IMPROVE THE ABILITY IN USING PUNCTUATION AMONG YEAR THREE PUPILS - Yee Bee Choo; Nurdalilah bte Razemi (Universitas Sembilanbelas November Kolaka, 2016)
The purpose of this research was to investigate the use of action song to improve the usage of punctuation among Year 3 pupils in a primary school in Johor. The whole class of eighteen pupils were selected as the target group. The teaching strategy comprised of the action song and the signs of punctuation marks such as full stop and comma. This study adopts a classroom action research. Tests, teacher’s reflective journal and interview were used to gather the data for the study. The findings showed improvement when comparing the pupils’ results in the tests before and after the implementation of action songs they were able to use the punctuations of full stop and comma correctly in the sentences. The findings also showed that the pupils were motivated to learn English and the strategy used improved the teacher’s teaching practice. A few suggestions were given to improve the strategy for the next cycle of action research.